The impact of smoking status on radiographic progression in patients with ankylosing spondylitis on anti-tumor necrosis factor treatment - Nam, Bora; Koo, Bon San; Choi, Nayeon; Shin, Ji-Hui; Lee, Seunghun; Joo, Kyung Bin; Kim, Tae-Hwan (Frontiers in Medicine, 2022)
Backgrounds: Ankylosing spondylitis (AS) is characterized by back pain which can lead to spinal ankylosis. Anti-tumor necrosis factor (TNF) dramatically alleviates symptoms, but spinal damage can still be progressive even during anti-TNF treatment. Smoking is a one of well-known risk factors for structural damage in AS. However, it has not been confirmed that smoking can affect radiographic progression even during anti-TNF treatment. Objective: To investigate factors associated with radiographic progression during anti-TNF treatment with a focus on smoking status which is known as one of poor prognostic factors for AS. Methods: We conducted a retrospective cohort study of AS patients who began the first-line anti-TNF treatment between 2001 and 2018 according to availability of smoking data. All enrolled patients were observed until the last visit, the first-line anti-TNF discontinuation, or December 2019. Radiographic damage was assessed using the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS). The mSASSS progression rate (units/year) was calculated using the baseline mSASSS, the final mSASSS during observation period, and the duration between them. Univariable and multivariable logistic regression analyses were performed to identify associated factors of mSASSS progression rate > 1 unit/year. Results: Among 459 AS patients, 185 (40.3%) patients were never smokers, 62 (13.5%) were ex-smokers and 212 (46.2%) were current smokers at baseline. Ex- and current smokers had higher mSASSS progression rates than never smokers (never smoker 0.1 [0.0-0.7], ex-smoker 0.6 [0.0-1.5], and current smoker 0.6 [0.0-1.5] units/year, P < 0.001). In the multivariable logistic analysis, current smoking (adjusted odds ratio [OR] 1.69, 95% CI 1.01-2.82, P = 0.047) and higher baseline mSASSS (adjusted OR 1.03, 95% CI 1.01-1.04, P < 0.001) were associated with a mSASSS progression rate > 1 unit/year. Conclusions: Current smoking is a modifiable risk factor for radiographic progression in patients with AS on anti-TNF treatment. Quitting smoking should be strongly recommended.